PENILAIAN KELAYAKAN OBJEK PUPIL DARI FRAME CITRA MATA PADA APLIKASI PEMERIKSA MYOPIA MENGGUNAKAN STANDAR DEVIASI - Mulyana, Teady Matius Surya; Herlina, Herlina (Universitas Tarumanagara, 2019)
The process of determining vision in patients with myopia based on computer vision requires image frames containing pupil objects that are deemed to meet the requirements before entering the vision determination stage. Image frame requirements that are considered to meet the requirements are image frames that contain objects that are not too small or too large. The extraction of eye image frames in real-time results in eye image frames being captured by the camera when the eyes are blinking, so that they contain too small pupil objects. The process of determining the threshold value in binaryization of an eye image that is too large also results in pupillary objects blending with the shadows around the eye, resulting in objects that are too large. Small samples in eye image taking require treatment for statistical assessment with small samples. The small number of samples can be used to determine the feasibility of the image to enter the next process can be implemented using standard deviations. Standard deviation values can accommodate the need to limit the size range of pupil objects in the eye image that is considered feasible. The final result of this study is the implementation of the method of determining an image considered to have a pupil object of a size that is suitable for observation so that the interval is obtained according to the conditions of each set of eye images recorded by the camera during eye observation. The use of standard deviations in determining which images are considered feasible contributes to increasing the percentage of accuracy of eye vision assessment in the application of myopia vision determination in real time from 54% without standard deviation to 73% in the confidence value for an average one-time interval of 99% in the process of determining myopia vision . AbstrakProses penentuan visus pada penderita myopia berbasis computer vision memerlukan frame-frame citra yang berisi objek pupil yang dianggap memenuhi persyaratan sebelum masuk ke tahap penentuan visus. Persyaratan frame-frame citra yang dianggap memenuhi persyaratan adalah frame-frame citra yang berisi objek dengan ukuran yang tidak terlalu kecil ataupun terlalu besar. Pengambalian frame-frame citra mata secara real-time mengakibatkan adanya frame citra mata yang ditangkap kamera ketika mata sedang berkedip, sehingga berisi objek pupil yang terlalu kecil. Proses penentuan nilai ambang pada binerisasi citra mata yang terlalu besar juga mengakibatkan objek pupil berbaur dengan bayangan di sekitar mata, sehingga menghasilkan objek yang terlalu besar. Sampel yang kecil pada pengambilan citra mata memerlukan perlakuan untuk penilaian statistik dengan sampel kecil. Jumlah sampel yang kecil dapat untuk menentukan kelayakan citra untuk masuk proses selanjutnya dapat diimplementasikan menggunakan standar deviasi. Nilai standar deviasi dapat mengakomodasi keperluan membatasi rentang ukuran objek pupil pada citra mata yang dianggap layak. Hasil akhir dari penelitian ini adalah implementasi metode penentuan suatu citra dianggap memiliki objek pupil dengan ukuran yang layak untuk diobservasi sehingga didapatkan interval yang sesuai kondisi masing-masing set citra mata yang direkam oleh kamera pada saat observasi mata. Penggunaan standar deviasi pada penentuan citra yang dianggap layak berkontribusi menaikkan persentase ketepatan penilaian visus mata pada aplikasi penentuan visus myopia secara real time dari 54% tanpa standar deviasi menjadi 73% pada nilai confidence untuk interval satu rata-rata sebesar 99% pada proses penentu visus myopia.